2011
DOI: 10.1128/aem.01798-10
|View full text |Cite
|
Sign up to set email alerts
|

GeoChip-Based Analysis of the Functional Gene Diversity and Metabolic Potential of Microbial Communities in Acid Mine Drainage

Abstract: Acid mine drainage (AMD) is an extreme environment, usually with low pH and high concentrations of metals. Although the phylogenetic diversity of AMD microbial communities has been examined extensively, little is known about their functional gene diversity and metabolic potential. In this study, a comprehensive functional gene array (GeoChip 2.0) was used to analyze the functional diversity, composition, structure, and metabolic potential of AMD microbial communities from three copper mines in China. GeoChip d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 59 publications
6
51
0
Order By: Relevance
“…In the present study, the distLM approach was used to calculate the significant influence of DDX compounds on the bacterial community structure, suggesting that the biogeochemical conditions at the dumping site influence the functional diversity of the bacterial community. The significant influence of environmental factors on the functional diversity of bacterial communities was previously reported in similar studies investigating the relationships between the diversity of functional genes and environmental factors (Waldron et al, 2009;Xie et al, 2011). Waldron and co-workers observed lower gene diversity in highly contaminated samples and the significant influence of contaminants on the functional structure of the bacterial communities, consistent with the results presented herein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the distLM approach was used to calculate the significant influence of DDX compounds on the bacterial community structure, suggesting that the biogeochemical conditions at the dumping site influence the functional diversity of the bacterial community. The significant influence of environmental factors on the functional diversity of bacterial communities was previously reported in similar studies investigating the relationships between the diversity of functional genes and environmental factors (Waldron et al, 2009;Xie et al, 2011). Waldron and co-workers observed lower gene diversity in highly contaminated samples and the significant influence of contaminants on the functional structure of the bacterial communities, consistent with the results presented herein.…”
Section: Discussionsupporting
confidence: 92%
“…Molecular approaches, such as functional gene arrays, facilitate a relatively easy assessment of the information in the microbenthic community, including community structure and function (Lu et al, 2012). Various studies have demonstrated the capacity of functional gene arrays to detect microbial community responses to environmental stressors Liu et al, 2010;Wang et al, 2009;Ward et al, 2007;Wu et al, 2008;Yergeau et al, 2007;Zhou, 2003), including heavily contaminated habitats (Lu et al, 2012;Neufeld et al, 2006;Van Nostrand et al, 2009;Xie et al, 2011). The results of these studies and other approaches evaluating the response of bacterial communities on environmental perturbation (chemically or physically) have demonstrated changes in the respective community structure and function (dos Santos et al, 2011;Findlay et al, 1990;Suarez-Suarez et al, 2011), thereby forming the basis for our hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater and sludge properties (Table S2 and Table S3) were standardized to have comparability prior to further analysis using the formula, z ¼ ðx i À xÞ=s, where x i is the sample value, x is the mean of all samples, and s is the standard deviation on (Freeman, 1994;Xie et al, 2011). Diversity indices including Shannon-Weaver H and Simpson were calculated using R 2.9.1 (http://www.r-project.org/) with the vegan package to evaluate the microbial functional diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The most comprehensive microbial functional microarray to date, the GeoChip 4.0, targets 410 000 sequences represented by 150 genes mainly from soil microbial communities and reductionoxidation processes (He et al, , 2010; Bai et al, 2013;Zhou et al, 2013). In addition to contaminated soils, acid mine drainage sites and Antarctic soils (Yergeau et al, 2007;Mason et al, 2010;Xie et al, 2011), the GeoChip has been applied to detect microbial DNA and RNA in the marine environment (Lu et al, 2012;Wawrik et al, 2012). Aside from the PhyloChip, which targets 16S rRNA genes (Brodie et al, 2006), existing microarrays target a specific genus (Rinta-Kanto et al, 2011), a particular process (Tiquia et al, 2004;Moisander et al, 2006Moisander et al, , 2007Ward et al, 2007;Bulow et al, 2008;Wu et al, 2008;Bouskill et al, 2011;Abell et al, 2012) or ecosystem (Rich et al, 2008;Smith et al, 2010;Rich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%